Integrating radiology vertically into an undergraduate medical education curriculum: a triphasic integration approach - Al Qahtani F; Abdelaziz A (Advances in Medical Education and Practice, 2014)
Fahd Al Qahtani,1 Adel Abdelaziz2,31Radiology Department, Faculty of Medicine, Al-Baha University, Al-Baha, Saudi Arabia; 2Medical Education Development Unit, Faculty of Medicine, Al-Baha University, Al-Baha, Saudi Arabia; 3Medical Education Department, Faculty of Medicine, Suez Canal University, Ismailia, EgyptAbstract: Fulfilling the goal of integrating radiology into undergraduate medical curricula is a real challenge due to the enduring faith assuming that traditional medical disciplines are worthy of consuming the available study time. In this manner, radiology is addressed occasionally and with relevance to these traditional disciplines. In Al-Baha University Faculty of Medicine, Al-Baha, Saudi Arabia, efforts have been made to integrate radiology vertically and in a structured manner into the undergraduate curriculum from the first year to the sixth year. For achieving convenient integration of radiology, a triphasic approach to integration is adopted. This approach consists of the integration of radiology foundations into the basic sciences phase, development of a distinct 4-week module in year 4, and finally, integration of clinical applications of radiology in the clinical phase modules. Feedback of students and inferences obtained through assessment and program evaluation are in favor of this approach to integration. Minor reform and some improvement related to time allocated and content balancing are still indicated.Keywords: radiology foundations, radiology module, students assessment